Analysis of Higher Order Thinking Skills (HOTs) in English Final Examination Questions at Junior High School - Lestari, Esti Sapta; Widi Pratolo, Bambang (ETERNAL (English Teaching Journal), 2025)
The development of students' Higher Order Thinking Skills (HOTs) is emphasized in the Indonesian educational system. The aim of this research was to examine the HOTs found in the English final exam questions for the 2023–2024 academic year at private schools in Yogyakarta. The test questions were categorized into higher-order thinking skills (HOTs) and lower-order thinking abilities (LOTs) using the updated Bloom's taxonomy framework. The purpose of this study is to determine how much final examination questions at private junior high schools for the academic year 2023–2024 foster higher-order thinking abilities and to pinpoint areas that could use development in order to better support the curriculum objectives. Qualitative content analysis design was used in this research. The data resources of this research were the final exam test questions for the academic year 2023–2024. The revised Bloom’s taxonomy framework was used to analyze the data. The findings of this research indicated that the test questions demand more HOTs-type questions since the exams are predominantly LOTs-type questions. Most of the test questions (46.7%) are about applying questions, followed by comprehending (37.8%) and analysis (15.5%). The results revealed that the exam questions lacked HOTs-type questions.